Reproductive and productive characteristics of hair sheep raised in the tropical region grassland of Brazil (Research, Society and Development, 2020)
We aimed to characterize the energetic profile of hair sheep (Ovis aries) raised on pasture in a tropical climate country and verify it is influence on productive and reproductive parameters. A total of 68 non-pregnant adult ewes were randomly distributed into four genetic groups (GGs) according to coat color (Red-coated Santa Inês GG – 17, Black-coated Santa Inês GG – 13, White-coated Morada Nova GG – 28 and Red-coated Morada Nova GG – 10). We collected blood samples at the beginning and at the end of the breeding season. The reproductive efficiency of the ewes was evaluated by fertility, prolificacy, lamb survival rate, and lamb body weight at birth and weaning. We performed statistical analyses using the package PROC GLM and the chi-square (χ2) test from SAS software. The genetic group influenced serum glucose and β-hydroxybutyrate concentrations, prolificacy, and lamb body weight. Male lambs were heavier than female lambs at birth and weaning. Twin lambs were lighter at birth and at weaning than were single lambs. The genetic group, lamb birth rank, and sex influenced the lamb body weight at birth and weaning. This study presents important information on the reproductive efficiency of these hair sheep that are relevant to tropical climate countries. The blood parameters found in this research show that there are important metabolic differences between hair sheep in the semi-arid region of Northeast Brazil. Morada Nova sheep with independent white coat color, higher reproductive performance in tropical conditions.